Reasoning and Action: Implementation of a Decision-Making Program in Sport. (20th September 2016) - Gil-Arias, Alexander; Moreno, M. Perla; García-Mas, Alex; Moreno, Alberto; García-González, Luíz; del Villar, Fernando
Abstract: The objective of this study was to apply a decision training programme, based on the use of video-feedback and questioning, in real game time, in order to improve decision-making in volleyball attack actions. A three-phase quasi-experimental design was implemented: Phase A (pre-test), Phase B (Intervention) and Phase C (Retention). The sample was made up of 8 female Under-16 volleyball players, who were divided into two groups: experimental group ( n = 4) and control group ( n = 4). The independent variable was the decision training program, which was applied for 11 weeks in a training context, more specifically in a 6x6 game situation. The player had to analyze the reasons and causes of the decision taken. The dependent variable was decision-making, which was assessed based on systematic observation, using the "Game Performance Assessment Instrument" (GPAI) (Oslin, Mitchell, & Griffin, 1998 ). Results showed that, after applying the decision training program, the experimental group showed a significantly higher average percentage of successful decisions than the control group F (1, 6) = 11.26; p = .015; η 2 p = .652; 95% CI [056, 360]. These results highlight the need to complement the training process with cognitive tools such as video-feedback and questioning in order to improve athletes' decision-making.